Amalgamation of diverse hydrodynamic effects with novel triple-sided membrane valves for developing a microfluidic device for filterless and continuous water purification. Issue 46 (25th August 2021) - Prabhakar, Amit; Jaiswar, Ankur; Mishra, Neha; Kumar, Praveen; Dhwaj, Amar; Nayak, Prashant; Verma, Deepti
Abstract : A microfluidic device displaying multiple hydrodynamic effects was designed to separate suspended impurities ( i.e. bacteria and similar length scale particles present in water in the suspension form) from water. Abstract : The requirement for clean water has been increasing for several reasons, for instance, the fast industrialization of developing countries, climate change, environmental pollution, growth of biofuel use and the resulting growth in irrigation. To meet the requirements for contamination-free water, a cost-effective water treatment can substantially improve the developing world's health, largely for children, and there is predicted to be a huge market for this. Existing water treatment processes consist of various phases that are time-consuming as well as pricey. There is an essential demand for cost-effective point of use methods to purify drinking water to reduce the impact of diseases induced by numerous waterborne pathogens. The development of micro-devices, with different outcomes, can be a helpful solution to various problems. To make this reality, a novel microfluidic device for the purification of water, with multiple hydrodynamic effects, has been shown in this paper. In the proposed novel device, the network of interconnected microfluidic channels was created in such a way that an amalgamation of multiple effects, such as the Fåhræus effect, centrifugal force, the Zweifach–Fung effect and constriction followed by expansion, act together in the microchannel to separate suspended impurities ( i.e. bacteria and similar length scale particles present in water in the suspension form) from water. Furthermore, to improve the bacterial separation efficiency of the device, the pure water channel of the microdevice was designed with an encircled triple-sided film valve arrangement at a few points, which aided the modulation of the cross-sectional area of the pure water channel. Consecutively, the reduction of the cross-sectional area of the pure water channel caused a highly effective Zweifach–Fung effect, which aided the better separation of the suspended particles ( i.e. bacteria, dust particles etc. ). The device was observed to have an average of 99.6% efficiency in the separation of suspended microparticles/microbes with dimensions in the range of 1–10 micrometres. The device performance indicated its potential for the separation of other similar suspended impurities, i.e. small dust particles, bacteria, fungi, viruses and similar particles present in water in the suspension form.